Building Resilience to Climate Change: A Case Study of Female Headed Households in Arid Region of Buhera District, Zimbabwe - Ruparanganda, L.; Nyoni, C. (Springer, Singapore, 2022)
Climate change is increasingly recognised as a global phenomenon with potentially far reaching implications. Sub- Saharan Africa has already started experiencing climate change. It is threatening food security with vulnerable groups who include female headed households most likely to suffer due to their heavy reliance on rain-fed systems to supplement household food security. This paper sought to explore strategies employed by female heads in building resilience to the effects of climate change. This was done by analyzing adaptation strategies employed by female heads in responding to climate change induced food insecurity as well as limitation to adaptation. An approach based on the understanding that resilience is a function of adaptation. The study is based on the action oriented theory of adaptation by Klaus I, 2011 as basis for understanding social action processes shaping climate change resilience building processes within female headed households. It makes use of the qualitative research approach through application of case study research design in which in-depth interviews, key informant interviews and focus group discussions were used to collect data. Findings from the study reflect that whilst female headed households have adopted numerous coping and adaptation mechanisms in building resilience to the threats of climate change on food security which include cultivation of traditional grains, shifting planting dates and diversifying livelihoods through participation in community savings groups and extraction of non-timber products for sale. Female heads remain constrained in their ability to adopt a wide range of local available adaptation strategies due to existing socio-cultural barriers, lack of resources and gender imbalances. Hence, the importance of designing policies, programs and implementation strategies that is gender sensitive for maximum benefit by female heads.